Can operational efficiency in the Portuguese electricity sector be improved? Yes, but... - Zheng, H.; Roseta-Palma, C.; Ramalho, J. J. S. (Energy Policy, 2024)
Efficiency has long been an issue of concern in the electricity sector. Most existing studies relate technical efficiency in electricity generation to policy factors while that in transmission and distribution is associated with environmental factors. Although firm operation is also a relevant perspective on this topic, its explicit impact upon technical efficiency has rarely been studied. In order to analyze the evolution and operational determinants of productive and cost efficiency in the Portuguese electricity sector (including generation from different sources, trade, transmission and distribution), this study estimates Stochastic Frontier models using firm-level panel data from 2006 to 2019, covering the period of liberalization of the Portuguese electricity market. The evidence indicates efficiency improvement through time, which is likely to slow down and needs to be consolidated. Results on the inefficiency determinants suggest that it is possible to improve productive technical efficiency by encouraging investment in fixed assets, higher average hourly wage and moderate average working hours. In addition, based on the results, we advocate deepening the integration of the Iberian electricity market and stimulating competition in the renewable energy sector.